A kind of anti-aging heat-resistant polyglycolide injection molding material and preparation method thereof

By improving the formulation of polyglycolide injection molding materials and adding components such as PBS or PBAT and talc, the problem of the rapid aging of existing biodegradable resins in high temperature and high humidity environments has been solved, and the material's anti-aging and heat resistance is improved.

CN116120726BActive Publication Date: 2025-03-04HUZHOU GLOBAL XINYIFENG ENVIRONMENTAL PROTECTION TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310080973.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2025-03-04
Estimated Expiration
2043-02-08

AI Technical Summary

Technical Problem

Existing biodegradable resins such as PLA are aging rapidly in high temperature and high humidity environments, resulting in product embrittlement, and the thermal deformation temperature of their injection molded materials is insufficient, affecting use and transportation.

Method used

An anti-aging heat-resistant polyglycolide (PGA) injection molding material is prepared by drying, mixing and extrusion processes using a main polymer PGA, reinforced polymer PBS or PBAT, anti-hydrolyzer, lubricant, filler talc and heterophase nucleating agent talc.

Benefits of technology

It delays the aging process of the material, improves the mechanical properties and heat resistance of the material, reduces the aging speed, and extends the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of degradable polymer compounds, and in particular to an anti-aging heat-resistant polyglycolide injection molding material and a preparation method thereof. The polyglycolide injection molding material comprises, by mass percentage, the following: a main polymer, 45-85%; a reinforcing polymer, 5-15%; an anti-hydrolysis agent, 0.1-1%; a lubricant, 0.1-0.5%; a filler, 5-25%; and a heterogeneous nucleating agent, 3-15%. The main polymer is PGA, the reinforcing polymer is PBS and / or PBAT, and the filler and the heterogeneous nucleating agent are both selected from talcum powder. The toughness of the injection molding material is improved due to the addition of PBS or PBAT. In addition, two types of talcum powders of different particle sizes are used as fillers and heterogeneous nucleating agents, respectively, and after compounding, the mechanical properties of the material can be improved and the aging process of the material can be delayed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of degradable polymer compounds, and in particular to an anti-aging heat-resistant polyglycolide injection molding material and a preparation method thereof. Technical Background

[0002] In recent years, with the improvement of people's environmental awareness and the implementation of plastic bans in various countries, products made of biodegradable materials have gradually become popular. Biodegradable materials are degraded through composting, soil, etc., and the final products are water and carbon dioxide. At present, in addition to natural biodegradable materials such as wood, bamboo, starch, etc., the biodegradable resins obtained by synthesis mainly include polylactic acid (PLA), terephthalic acid-butylene adipate copolymer (PBAT), etc. The molecular structure of these materials is polyester-type. Products made from these biodegradable resins will gradually degrade and age during the storage period due to the hydrolysis of ester bonds, resulting in embrittlement. Especially for some products that are used many times, there is sometimes a high temperature and high humidity environment during use, and the aging speed of the materials is faster.

[0003] At present, the biodegradable resins produced on a large scale worldwide mainly include PLA, PBAT and PBS. PLA resin has a wider range of applications due to its excellent comprehensive performance. It has been widely used in coating, sheet, injection molding, film and 3D printing. However, due to the slow crystallization speed of PLA, the products obtained by conventional molding are basically not heat-resistant, and the heat deformation temperature is only about 55°C. Especially in the field of injection molding materials, the low heat deformation temperature affects the use on the one hand, and it is also easy to deform due to insufficient heat resistance during transportation on the other hand. Therefore, at present, PLA injection molding products need to be crystallized in or out of the mold to achieve a certain temperature resistance. In-mold crystallization affects the production efficiency of the product, and out-of-mold crystallization will cause a certain deformation of the product. At the same time, the hardware investment and energy consumption of the product are nearly doubled. PLA materials can be degraded quickly under composting conditions, but they degrade very slowly in soil environments and are more difficult to degrade in marine environments.

[0004] For this reason, people have turned their attention to other biodegradable materials, such as polyglycolide (PGA), which, as a fully biodegradable resin, can not only be degraded under composting conditions, but also quickly degrade in natural soil and seawater environments. At the same time, PGA has a temperature resistance of more than 120°C, and the rigidity and toughness of the material are very good. From the comprehensive performance point of view, it is a heat-resistant biodegradable material that is very suitable for injection molding. However, PGA has the shortest weight unit and is the fastest degradable among aliphatic polyesters. Its low molecular weight product is an ideal inducer of complete microbial degradation. Too fast a degradation rate can easily cause the product to age and become brittle during the storage period, thus losing the product's performance.

[0005] In the prior art, there is also a material technology that uses PGA as one of the raw materials, such as the Chinese invention patent with application publication number CN 114045015A, which discloses a fully biodegradable foaming net and a preparation method thereof. The foaming net contains the following components in parts by mass: 40-85 parts of PBAT, 10-30 parts of PBS, 5-30 parts of PGA, 0.4-1 parts of a compatibilizer, 0.4-1 parts of an anti-hydrolysis agent, 0.8-2 parts of an organic nucleating agent, 2-4 parts of an inorganic nucleating agent, 0.3-0.5 parts of a lubricant, 0.2-0.3 parts of an anti-shrinkage agent, 0.4-1 parts of an antioxidant, and 2 parts of a masterbatch. The provided foaming net material has the characteristics of being fully degradable in the natural domain, especially in the water body of the marine environment. It also has the ability to degrade, and the degradation time can be regulated, so that the shelf life of the foaming net product is extended. Summary of the invention

[0006] In order to solve the above technical problems, the inventors of the present application have found a new way to improve the formula of polyglycolide injection molding material in order to delay the aging of the material and obtain products with excellent mechanical properties under this premise.

[0007] One of the purposes of the present invention is to provide an anti-aging heat-resistant polyglycolide injection molding material, and the second purpose is to provide a preparation method of the polyglycolide injection molding material.

[0008] The specific technical solutions are described below:

[0009] An anti-aging heat-resistant polyglycolide injection molding material comprises the following components in parts by mass:

[0010] Main polymer, 45-85 parts;

[0011] Reinforcing polymer, 5-15 parts;

[0012] Anti-hydrolysis agent, 0.04~1 part;

[0013] Lubricant, 0.01~0.5 parts;

[0014] Filler, 5-25 parts;

[0015] Heterogeneous nucleating agent, 3-15 parts;

[0016] Wherein, the main polymer is PGA, and the reinforcing polymer is PBS and / or PBAT, the English abbreviation PGA is polyglycolide, PBS is polybutylene succinate, and PBAT is polybutylene adipate / terephthalate;

[0017] The filler and the heterogeneous nucleating agent are both selected from talc.

[0018] In this technical solution, the addition of PBS or PBAT can improve the toughness of PGA. In addition, the terminal carboxyl content in PBS or PBAT resin will also significantly affect the aging performance of the material. The higher the terminal carboxyl content, the faster the material ages. Preferably, the terminal carboxyl content of the reinforcing polymer is less than 30 mol / t, more preferably, the terminal carboxyl content is less than 15 mol / t, and most preferably, the terminal carboxyl content of PBS is less than 10 mol / t.

[0019] In the polyglycolide injection molding material formula involved in the invention, talcum powder is innovatively used as both a filler and a heterogeneous nucleating agent. Functionally, the talcum powder used as a filler has a relatively large particle size based on the basic function of a filler; while the talcum powder used as a heterogeneous nucleating agent has a relatively small particle size based on the need for heterogeneous nucleation.

[0020] The inventor believes that after compounding two types of talcum powder with different particle sizes, at least the following beneficial effects are achieved:

[0021] ① It can improve the mechanical properties of polyglycolide injection molding materials, which is reflected in the reinforcing effect of talcum powder as a filler on the material, and the promotion of talcum powder as a heterogeneous nucleating agent on PGA crystallization. The crystallinity is improved, which can also improve some mechanical properties of the material;

[0022] ②Talc itself is weakly alkaline, which is beneficial to delay the aging process of PGA, PBS and PBAT;

[0023] ③After testing, it was found that talc powder as a filler not only brought a reinforcing effect to the material, but also improved the crystallization effect of the PGA material. This should be because the addition of large-particle filler talc powder played a spacing effect, which weakened the agglomeration effect of small-particle heterogeneous nucleating agent talc powder, thereby increasing its dispersion in the material and promoting crystal formation;

[0024] In other words, talcum powder as a filler not only plays a reinforcing role from the filling perspective, but also plays a role in enhancing the mechanical properties of the material from the perspective of improving the crystallization effect of PGA materials.

[0025] Talc as a filler needs to have a certain particle size range as the basis for the enhancement effect. Preferably, the filler is talc with a mesh size of 800-3000 mesh; further preferably, the filler is talc with a mesh size of 1000-2000 mesh, and the addition amount is 10-25 parts.

[0026] Talc powder as a heterogeneous nucleating agent needs to reach a certain fineness to have a nucleating effect. Preferably, the heterogeneous nucleating agent is talc powder with a mesh number of 3000-10000 mesh; further preferably, the heterogeneous nucleating agent is talc powder with a mesh number of 5000-10000 mesh, and the addition amount is 5-12 parts.

[0027] The anti-hydrolysis agent has a carbodiimide structure, can react with the terminal carboxyl groups and hydrolyzed carboxylic acids of PGA, PBS and PBAT, prevent the degradation of autocatalytic hydrolysis, and improve the aging resistance and service life of the material. Preferably, the anti-hydrolysis agent is selected from one of HyMax 1010 and HyMax 210, preferably HyMax210, and the addition amount of the anti-hydrolysis agent is 0.5 to 1 part.

[0028] The addition of lubricant is beneficial to the stable processing and injection molding demoulding of the material. Preferably, the lubricant is selected from one or more of EBS, PE wax and erucamide, and the added amount is preferably 0.3-0.5 parts.

[0029] The method for preparing the polyglycolide injection molding material described in any of the above technical solutions comprises the following steps:

[0030] Drying: Drying the main polymer and the reinforcing polymer, and making sure that the moisture content of the dried main polymer and the reinforcing polymer is within 200ppm; Drying the filler and the heterogeneous nucleating agent, and controlling the moisture content of the dried filler and the heterogeneous nucleating agent to be within 0.15%;

[0031] Mixing: Put the dried main polymer, reinforcing polymer, anti-hydrolysis agent and lubricant into a mixer and mix them evenly to form a mixed material;

[0032] Extrusion: The mixed material is fed into a screw extruder for melt mixing and extrusion at a temperature range of 210-225°C. The dried filler and heterogeneous nucleating agent are fed into the screw extruder and mixed evenly with the molten material. At the same time, the vacuum degree of the vacuum system of the screw extruder is ensured to be above -0.08MPa to further remove the residual monomers of PGA. The extruded material strips are air-cooled and drawn before pelletizing and packaging.

[0033] Preferably, in the drying step, the main polymer and the reinforcing polymer are dried in a dehumidifying dryer at 55-70°C for 4-6 hours, so that the dew point temperature of the dehumidifying dryer is below -50°C; the filler and the heterogeneous nucleating agent are stirred in a stirrer with a heating function for 1-2 hours for drying, and the stirring temperature is 80-100°C.

[0034] In summary, the technical solution of the present invention has the following main beneficial effects:

[0035] The PGA injection molding material described in the embodiment of the present invention has improved toughness due to the addition of PBS or PBAT.

[0036] In addition, two types of talc powder with different particle sizes can be compounded as fillers and heterogeneous nucleating agents to improve the mechanical properties of the material and delay the aging process of the material.

[0037] Further or more detailed beneficial effects will be described in detail in conjunction with specific examples in the specific implementation manner. DETAILED DESCRIPTION

[0038] The present invention will be further explained below in conjunction with embodiments:

[0039] It should be noted that the embodiments do not constitute a limitation on the protection scope of the claims of the present invention. According to the technical concepts provided / proven by the embodiments, all technical solutions that can be reasonably anticipated by technicians in the relevant technical field should be included in the protection scope of the claims of the present invention.

[0040] The evaluation methods or standards for the sample performance involved in this embodiment / comparative example are as follows:

[0041] Heat Deflection Temperature :

[0042] The obtained specimens were tested for heat resistance - heat deformation temperature of the material under a pressure of 0.45 MPa using an MIT-300AT-3 heat deformation temperature tester produced by Bangyi Precision Measuring Instruments (Shanghai) Co., Ltd.

[0043] Tensile Strength :

[0044] According to the standard: GB\T1040.3-2006 Determination of tensile properties of plastics Part 3, the test conditions for films and sheets are: dumbbell-shaped specimens with a length of 150 mm, a narrow parallel width of 10 mm, a tensile speed of 50 mm / min, and a room temperature of 25°C.

[0045] Crystallinity :

[0046] The crystallinity of the samples was determined by x-ray diffraction;

[0047] Specifically, the crystallinity of the sample was quantitatively analyzed by using the Miniflex600 x-ray diffractometer of Rigaku Corporation of Japan through the full spectrum fitting analysis with Rietvelt refinement;

[0048] Specifically, Cu radiation was used to scan in the range of 5-50° with a scanning step of 0.05°. The crystallinity (%) was expressed as the ratio of the crystal area under the X-ray diffraction peak to the total area:

[0049] X c %=[S c / (S a +S c )]×100%

[0050] Where, X c is the crystallinity;

[0051] S c is the area of ​​the crystalline phase;

[0052] S a is the area of ​​the amorphous phase;

[0053] (S a +S c ) is the total area under the X-ray diffraction peak.

[0054] Melt flow rate :

[0055] The WKT-400 melt flow anemometer produced by Jiangsu Weiket Instrument Co., Ltd. was used to test the melt flow rate of PGA raw materials and specimens before and after aging. The measuring conditions were: temperature 235°C, load 2160g, and pressure on the sample 0.2982Mpa.

[0056] Aging conditions :

[0057] Aging for 100 hours in a constant temperature and humidity aging box at 65°C and 50% humidity.

[0058] The embodiments and comparative examples are described in detail as follows:

[0059] Example 1 :

[0060] PGA with a melt flow rate of 10g / 10min and PBS with a terminal carboxyl content of 14mol / t were dried at 60℃ in a dehumidifying dryer for 5 hours, and 5000 mesh talc and 1000 mesh talc were dried and mixed at 90℃ in a low-speed mixer at a ratio of 1:2 for 1.5 hours. After drying, the moisture content of PGA was 180ppm, the moisture content of PBS was 150ppm, and the moisture content of talc was 0.13%. Then PGA, PBS, anti-hydrolysis agent HyMax 1010, and lubricant EBS were mixed evenly at high speed in a high-speed mixer;

[0061] The mixed materials enter the twin-screw extruder for melt mixing, extrusion and granulation. The extrusion temperature is 215°C. The dried talcum powder is added to the twin-screw extruder through side feeding and mixed evenly with the molten materials. The vacuum degree of the vacuum pump of the twin-screw extruder is about -0.085MPa. The extruded material strips are cooled by air-cooled drag chains, cut and packaged in time.

[0062] The mass fractions of each material are:

[0063] PGA, 59.2 copies;

[0064] PBS, 10 portions;

[0065] HyMax 1010, 0.05 parts;

[0066] EBS, 0.03 parts;

[0067] 5000 mesh talc, 6.93 parts;

[0068] 1000 mesh talcum powder, 13.86 parts.

[0069] Example 2 :

[0070] PGA with a melt flow rate of 15g / 10min and PBS with a terminal carboxyl content of 10mol / t were dried at 65℃ in a dehumidifying dryer for 4.5 hours. Talc powder of 7000 mesh and talc powder of 1250 mesh were dried and stirred in a low-speed mixer at 95℃ for 2 hours in a ratio of 8:20. After drying, the moisture content of PGA was 160ppm, the moisture content of PBS was 140ppm, and the moisture content of talc powder was 0.12%. Then PGA, PBS, anti-hydrolysis agent HyMax 1010, and lubricant PE wax were mixed evenly at high speed in a high-speed mixer;

[0071] The mixed materials enter the twin-screw extruder for melt mixing, extrusion and granulation. The extrusion temperature is 210°C. The dried talcum powder is added to the twin-screw extruder through side feeding and mixed evenly with the molten materials. The vacuum degree of the vacuum pump of the twin-screw extruder is about -0.09MPa. The extruded material strips are cooled by air-cooled drag chains, cut and packaged in time.

[0072] The mass fractions of each material are:

[0073] PGA, 56.94;

[0074] PBS, 15 portions;

[0075] HyMax 1010, 0.04 parts;

[0076] PE wax, 0.02 parts;

[0077] 7000 mesh talc, 5.76 parts;

[0078] 1250 mesh talc, 14.4 parts.

[0079] Example 3 :

[0080] PGA with a melt flow rate of 18g / 10min and PBAT with a terminal carboxyl content of 13mol / t were dried in a dehumidifying dryer at 60°C for 5 hours, and 10000 mesh talc and 800 mesh talc were dried and mixed in a low-speed mixer at 100°C for 1.5 hours in a ratio of 6:22. After drying, the moisture content of PGA was 140ppm, the moisture content of PBAT was 120ppm, and the moisture content of talc was 0.10%. Then PGA, PBAT, anti-hydrolysis agent HyMax 210, and lubricant erucamide were mixed evenly at high speed in a high-speed mixer;

[0081] The mixed materials enter the twin-screw extruder for melt mixing, extrusion and granulation. The extrusion temperature is 212°C. The dried talcum powder is added to the twin-screw extruder through side feeding and mixed evenly with the molten materials. The vacuum degree of the vacuum pump of the twin-screw extruder is about -0.09MPa. The extruded material strips are cooled by air-cooled drag chains, cut and packaged in time.

[0082] The mass fractions of each material are:

[0083] PGA, 65.94;

[0084] PBAT, 18 parts;

[0085] HyMax 210, 0.05 parts;

[0086] Erucamide, 0.01 part;

[0087] 10000 mesh talc, 4.68 parts;

[0088] 800 mesh talcum powder, 17.16 parts.

[0089] Comparative Example 1 :

[0090] Comparative Example 1 uses only PGA as extrusion material:

[0091] PGA with a melt flow rate of 10g / 10min was dried at 70°C in a dehumidifying dryer for 4 hours. The moisture content of PGA after drying was 150ppm. The dried PGA entered a twin-screw extruder for melt mixing, extrusion and granulation. The processing temperature was 215°C and the vacuum degree of the vacuum pump of the twin-screw extruder was about -0.09MPa. The extruded material strips were cooled and cut by an air-cooled drag chain and packaged in time.

[0092] Comparative Example 2 :

[0093] Comparative Example 2 uses only PLA (polylactic acid) as the extrusion material:

[0094] PLA with a melt flow rate of 12g / 10min was dried in a dehumidifying dryer at 70°C for 4 hours. After drying, the moisture content of PLA was 160ppm. The dried PLA entered a twin-screw extruder for melt mixing, extrusion and granulation. The processing temperature was 180°C, and the vacuum degree of the vacuum pump of the twin-screw extruder was about -0.09MPa. The extruded material strips were cooled and cut by an air-cooled drag chain and packaged in time.

[0095] The product test data of Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 1:

[0096] Table 1 Product test data of Examples 1 to 3 and Comparative Examples 1 to 2

[0097]

[0098] In the above test parameters, the higher the heat deformation temperature, the better the heat resistance of the material; the higher the melt flow rate of the material after aging treatment, the faster the aging speed of the material.

[0099] It can be seen from Table 1 that, relative to the single-component PGA injection molding material (Comparative Example 1), the injection molding materials prepared in Examples 1 to 3 have a significant improvement in aging resistance, and a slight improvement in toughness and heat resistance; and relative to the single-component PLA injection molding material (Comparative Example 2), the injection molding materials prepared in Examples 1 to 3 have a significant improvement in heat resistance, and a significant improvement in toughness.

[0100] Regarding the technical concept of using talc powder as both filler and heterogeneous nucleating agent in the formula, the inventors designed the following comparative examples 3 to 5 to verify the effect of talc powder with larger particle size as filler on material properties:

[0101] Comparative Example 3 :

[0102] Compared with Example 1, the only difference is that 1000 mesh talc powder is not added as a filler.

[0103] Comparative Example 4 :

[0104] Compared with Example 2, the only difference is that 1250 mesh talc powder is not added as a filler.

[0105] Comparative Example 5 :

[0106] Compared with Example 3, the only difference is that 800 mesh talc powder is not added as a filler.

[0107] The product test data of Examples 1 to 3 and Comparative Examples 3 to 5 are shown in Table 2:

[0108] Table 2 Product test data of Examples 1 to 3 and Comparative Examples 3 to 5

[0109]

[0110] The polymer crystallization process is divided into two stages: nucleus formation and nucleus growth. Nucleus formation can be achieved through homogeneous nucleation or heterogeneous nucleation. The molecular chains of PGA material molecules are relatively rigid, and the speed of forming nuclei through the orderly arrangement of their own molecular chains during cooling is very slow. Therefore, the crystallization speed of PGA through homogeneous nucleation is very slow. By adding dispersed small-sized particles to the polymer melt to adsorb the polymer chains in the melt for orderly arrangement to form nuclei, the small-sized particles act as heterogeneous nucleating agents for the polymer. In this way, the crystallization speed of PGA can be greatly improved. This is the reason for adding heterogeneous nucleating agents in the invention.

[0111] The particles of heterogeneous nucleating agent and polymer chain segments are basically in the same size range, specifically about 1 micron to 4 microns, and the corresponding mesh size is about 3500-14000 mesh. If the amount of heterogeneous nucleating agent added is too small, the nucleation effect is not obvious, and if the amount added is too large, it will cause cost waste.

[0112] After adding heterogeneous nucleating agent, the thermal crystallization temperature of PGA can be increased from about 110℃ to about 140℃, and the material has a wider crystallization temperature range during the cooling process. Since the glass transition temperature of PGA is only about 38℃, if the crystallinity of the material is not high, it is easy to soften and deform at a higher room temperature. After the crystallinity is improved, the tensile strength and thermal deformation temperature of the material will be improved. At the same time, after the crystallinity is improved, it is more difficult for moisture to invade the polymer crystallization area during the room temperature aging process of the material, which can delay the hydrolysis process of the polymer. In turn, the aging rate of the polymer is slowed down.

[0113] From the data comparison of Example 1-Comparative Example 3, Example 2-Comparative Example 4, and Example 3-Comparative Example 5 in Table 2, it can be seen that the direct impact of not adding talcum powder filler is the decrease in crystallinity. This should be because the relatively large particle size of the filler talcum powder has a certain spacing effect on the small particle size and easily agglomerated heterogeneous nucleating agent talc, which weakens the agglomeration effect of the heterogeneous nucleating agent talc, thereby increasing the dispersion degree of the heterogeneous nucleating agent in the material during the preparation process, which promotes the formation of heterogeneous crystals.

[0114] In Comparative Examples 3 to 5, due to the decrease in crystallinity, the tensile strength and heat deformation temperature of the materials decreased to varying degrees, and from the melt flow rate of the specimens before and after aging, it can be seen that the anti-aging properties of the samples prepared in Comparative Examples 3 to 5 also decreased to varying degrees.

[0115] It can be seen that talcum powder with increased particle size as a filler not only plays a role in reinforcing mechanical properties from the perspective of physical filling, but also can increase the overall crystallinity of the material, thereby improving the material's heat resistance, tensile strength and aging resistance.

[0116] The inventors continued to conduct in-depth research in order to further improve the heat resistance and anti-aging properties of the material products. By using a method of surface modification of only talcum powder with larger particles as a filler, the following comparative examples 6 to 8 were designed to verify the effects thereof.

[0117] Comparative Example 6:

[0118] Compared with Example 1, the only difference is that the 1000 mesh talc powder used as the filler is surface-modified, while the talc powder used as the heterogeneous nucleating agent is not surface-modified.

[0119] Comparative Example 7:

[0120] Compared with Example 2, the only difference is that the 1250 mesh talc powder used as the filler is surface-modified, while the talc powder used as the heterogeneous nucleating agent is not surface-modified.

[0121] Comparative Example 8:

[0122] Compared with Example 3, the only difference is that the 800-mesh talc powder used as the filler is surface-modified, while the talc powder used as the heterogeneous nucleating agent is not surface-modified.

[0123] For talc, surface modification by coupling agent and maleic anhydride graft are modification methods well known to those skilled in the art. However, for the sake of easy operation and cost saving, the talc of the invention tends to consider a simple blending modification method, which has low requirements on the production environment and equipment. Therefore, the surface modification method used in Comparative Examples 6 to 8 uses a silane coupling agent for modification, specifically:

[0124] The silane coupling agent KH-570 was prepared into a solution, stirred evenly, and the solution was dropped into the dried filler talcum powder, stirred for 60 minutes, and then heated and dried to obtain the modified filler talcum powder. The mass ratio of the filler talcum powder to KH-570 was 1:0.03.

[0125] As a conventional technical means in this field, coupling agents and maleic anhydride grafts are common surface modification methods. Those skilled in the art can easily learn that the use of maleic anhydride grafts and other types of coupling agents to modify the filler talc can also achieve corresponding technical effects. Therefore, the choice of modification method should not constitute a limitation on the scope of protection of the invention.

[0126] The product test data of Examples 1 to 3 and Comparative Examples 6 to 8 are shown in Table 3:

[0127] Table 3 Product test data of Examples 1 to 3 and Comparative Examples 6 to 8

[0128]

[0129] It can be seen from Table 3 that for the samples prepared in Comparative Examples 6 to 8, the modified filler talc can further improve the dispersion of the heterogeneous nucleating agent talc during the preparation of the samples, so that the crystallinity is further improved. Correspondingly, the heat resistance, tensile strength and aging resistance of the sample materials are also improved synchronously.

[0130] In addition, the inventors also conducted an in-depth analysis of the effect of the melt flow rate of PGA in the raw material on the performance of the finished material, and designed the following Examples 4 to 7 to verify the effects thereof.

[0131] Example 4 :

[0132] Compared with Example 1, the only difference is that the PGA melt flow rate in the raw material is 12 g / 10 min.

[0133] Example 5 :

[0134] Compared with Example 1, the only difference is that the PGA melt flow rate in the raw material is 15 g / 10 min.

[0135] Example 6 :

[0136] Compared with Example 1, the only difference is that the PGA melt flow rate in the raw material is 18 g / 10 min.

[0137] Example 7 :

[0138] Compared with Example 1, the only difference is that the PGA melt flow rate in the raw material is 21 g / 10 min.

[0139] The product test data of Examples 1, 4 to 7 are shown in Table 4:

[0140] Table 4 Product test data of Examples 1, 4 to 7

[0141]

[0142] Within a certain range, the higher the molecular weight of the polymer, the higher the relevant strength of the material, especially for rigid polymers such as PGA. The molecular weight of the polymer can be indirectly expressed by the melt flow rate. The lower the melt flow rate, the higher the molecular weight of the polymer. For polyester-based degradable materials such as PGA, the aging process of the material is actually a slow hydrolysis process. The hydrolysis is accompanied by a decrease in the molecular weight of the polymer, and the intuitive reaction is the increase in the melt flow rate. During the polymer aging process, the mechanical properties do not decrease significantly at the beginning, but in the later stage, as the molecular weight of the polymer decreases sharply, the mechanical properties of the material will also be lost rapidly. For example, when the molecular weight of the polymer decreases from 150,000 to 50,000, the mechanical properties only lose 10%, but when it decreases from 50,000 to 20,000, the mechanical properties lose 60%. Therefore, if the molecular weight of the polymer is larger in the early stage, the melt flow rate is lower, and the time left for the material to age is longer. At the same time, the molecular weight will also affect the heat resistance. The larger the molecular weight, the better the heat resistance of the material. From this perspective, the lower the melt flow rate of PGA as a raw material, the better.

[0143] However, the lower the melt flow rate of PGA, the larger the molecular weight of PGA. The increase in molecular weight is not conducive to the formation of the crystalline state of the material. Under the same crystallization conditions, the smaller the molecular weight of the material, the easier the molecular chain activity is, and the easier crystallization will occur. From this perspective, the higher the melt flow rate of PGA as a raw material, the better.

[0144] What is the effect of the melt flow rate of PGA as the main raw material on the material properties of the formulation system described in the invention?

[0145] Referring to the data in Table 4, from Example 1 to Example 4, and then to Example 7, the melt flow rate of PGA in the raw material gradually increases, which means that the molecular weight of PGA gradually decreases, and the data directly affected is the improvement of the crystallinity of the material.

[0146] The increase in crystallinity promotes the tensile strength, however, the gradual decrease in molecular weight has an adverse effect on the tensile strength. In the data of Examples 1 and 4 to 7, we see that the tensile strength of the sample materials increases first and then decreases. The inventors believe that this is due to the following: in the invented formulation system, within the PGA melt flow rate range of 10 to 15 g / 10 min, the effect of crystallinity on the tensile strength plays a dominant role, while within the PGA melt flow rate range of 15 to 21 g / 10 min, the molecular weight has a greater effect on the tensile strength.

[0147] From Example 1 to Example 4, and then to Example 7:

[0148] The heat deformation temperature of the sample material gradually increases, but the rate of increase gradually slows down. This is at least due to the fact that within the scope of the embodiment, the influence of crystallinity on the heat deformation temperature plays a dominant role, and as the melt flow rate decreases, the molecular weight of PGA gradually decreases, and the influence of the molecular weight on the heat deformation temperature gradually increases.

[0149] The aging resistance of the sample material gradually decreases. This is because within the scope of the embodiment, the molecular weight of the PGA raw material has a greater impact on the aging resistance, while the influence of the crystallinity on the aging resistance is second. As the melt flow rate decreases, the melt flow rate of the aged specimen of Example 7 has reached a relatively high level. Usually, within the formulation system of the present invention, the melt flow rate range of the PGA raw material is selected from 10~21g / 10min.

[0150] And further supplementary embodiments are as follows:

[0151] Example 8 :

[0152] Compared with Example 1, the only difference is the formula of the materials:

[0153] PGA, 85 copies;

[0154] PBAT, 15 parts;

[0155] HyMax 210, 1 part;

[0156] EBS, 0.5 parts;

[0157] 8000 mesh talcum powder, 15 parts;

[0158] 3000 mesh talcum powder, 25 parts.

[0159] Example 9 :

[0160] Compared with Example 1, the only difference is the formula of the materials:

[0161] PGA, 45 copies;

[0162] PBS, 5 portions;

[0163] HyMax 1010, 0.04 parts;

[0164] EBS, 0.02 parts;

[0165] 8000 mesh talcum powder, 5 parts;

[0166] 2000 mesh talcum powder, 10 parts.

[0167] Example 10 :

[0168] Compared with Example 1, the only difference is the formula of the materials:

[0169] PGA, 50 copies;

[0170] PBS, 10 portions;

[0171] HyMax 210, 0.05 parts;

[0172] Erucamide, 0.01 part;

[0173] 8000 mesh talcum powder, 3 parts;

[0174] 1200 mesh talcum powder, 5 parts.

[0175] Embodiment 11 :

[0176] Compared with Example 1, the only difference is the formula of the materials:

[0177] PGA, 60 parts;

[0178] PBS, 12 portions;

[0179] HyMax 1010, 0.04 parts;

[0180] EBS, 0.01 parts;

[0181] 5000 mesh talcum powder, 12 parts;

[0182] 1000 mesh talcum powder, 20 parts.

[0183] The product test data of Examples 8 to 11 are shown in Table 5:

[0184] Table 5 Product test data of Examples 8 to 11

[0185]

[0186] It can be seen from Table 5 that the samples prepared in Examples 8 to 11 all have good heat resistance, mechanical properties and aging resistance.

[0187] In the description of this specification, the description with reference to the terms "embodiment", "basic embodiment", "preferred embodiment", "other embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0188] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0189] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. An anti-aging heat-resistant polyglycolide injection molding material, characterized in that: According to the mass percentage, it contains the following components: Main polymer, 45-85 parts; Reinforcing polymer, 5-15 parts; Anti-hydrolysis agent, 0.04~1 part; Lubricant, 0.01~0.5 parts; Filler, 5-25 parts; Heterogeneous nucleating agent, 3-15 parts; Wherein, the main polymer is PGA, and the reinforcing polymer is PBS and / or PBAT; The filler and the heterogeneous nucleating agent are both selected from talc powder, the filler is talc powder with a mesh number of 1000-2000 meshes, and the heterogeneous nucleating agent is talc powder with a mesh number of 5000-10000 meshes.

2. The polyglycolide injection molding material according to claim 1, characterized in that: The added amount of the filler is 10 to 25 parts.

3. The polyglycolide injection molding material according to claim 1, characterized in that: The addition amount of the heterogeneous nucleating agent is 5 to 12 parts.

4. The polyglycolide injection molding material according to claim 1, characterized in that: The terminal carboxyl content of the reinforcing polymer is less than 30 mol / t.

5. The polyglycolide injection molding material according to claim 1, characterized in that: The anti-hydrolysis agent is selected from one of HyMax1010 and HyMax 210.

6. The polyglycolide injection molding material according to claim 1, characterized in that: The lubricant is selected from one or more of EBS, PE wax and erucamide.

7. The method for preparing the polyglycolide injection molding material according to any one of claims 1 to 6, characterized in that: It includes the following steps: Drying: Drying the main polymer and the reinforcing polymer, and making sure that the moisture content of the dried main polymer and the reinforcing polymer is within 200ppm; Drying the filler and the heterogeneous nucleating agent, and controlling the moisture content of the dried filler and the heterogeneous nucleating agent to be within 0.15%; Mixing: Put the dried main polymer, reinforcing polymer, anti-hydrolysis agent and lubricant into a mixer and mix them evenly to form a mixed material; Extrusion: The mixed material is fed into a screw extruder for melt mixing and extrusion at a temperature range of 210-225°C. The dried filler and heterogeneous nucleating agent are fed into the screw extruder and mixed evenly with the molten material. At the same time, the vacuum degree of the vacuum system of the screw extruder is ensured to be above -0.08MPa. The extruded material strips are air-cooled and drawn before pelletizing and packaging.

8. The preparation method according to claim 7, characterized in that: In the drying step, the main polymer and the reinforcing polymer are dried in a dehumidifying dryer at 55-70°C for 4-6 hours, so that the dew point temperature of the dehumidifying dryer is below -50°C; the filler and the heterogeneous nucleating agent are stirred in a mixer with a heating function for 1-2 hours for drying, and the stirring temperature is 80-100°C.

Citation Information

Patent Citations

  • Full-biodegradable foaming net and preparation method thereof

    CN114045015A

  • Full-biodegradable dental floss pick handle and preparation method thereof

    CN111154245A

  • Method for raising crystallization temperature of polyglycolic acid and polyglycolic acid resin composition having raised crystallization temperature

    JP2008260902A